Mayor Helen Boosalis : my mother's life in politics - Davis, Beth Boosalis (University of Nebraska Press, 2008)
Helen Boosalis's story, told by her daughter, Beth Boosalis Davis, is the story of a true pioneer of women in politics. The daughter of Greek immigrants, Boosalis achieved national prominence as the first woman president of the U.S. Conference of Mayors and as an outspoken advocate for economically distressed cities facing President Reagan's "new federalism." Winning the Democratic nomination for governor of Nebraska in 1986, Helen Boosalis ran against Kay Orr in the first gubernatorial contest between two women in U.S. history. The interwoven tales of conflict and challenge, from the mayor's.